Peningkatan Proses Pembelajaran Tematik Terpadu Dengan Menggunakan Model Kooperatif Tipe Group Investigation di Sekolah Dasar - Ayu Rahmadani; Nasrul Nasrul (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was to describe the improvement of integrated thematic learning process by using the Cooperative type Group Investigation model in class IV of SDN 18 Koto Tangah, Agam Regency. This type of research is Class Action Research (CAR) using a qualitative and quantitative approach. The research subjects were teachers and 20 grade IV students of SDN 18 Koto Tangah, Agam Regency. The use of the Cooperative type Group Investigation model in the learning process can improve student learning outcomes. this can be seen from the results of the first cycle, 76,80 point to 84,91 point in second cycle. Based on these results it can be concluded that using the Cooperative type Group Investigation model can improve the learning process.